Evaluating E-Government Maturity Using the Pillar Approach: A Focus on Situbondo Regency Government Official Website, Indonesia - Teresa Irmina Nangameka (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2022)
For almost 20 years, Indonesia has been committed to increasing the digitization of government through e-Government policies. Situbondo Regency, as the locus of this research 2021, received three Top Digital Awards 2021 from ITWorks Magazine for its success in running several digital-based public service innovations. Public service innovations include website development. The website becomes the primary tool to see the level of implementation of e-Government in a local government, the gateway to various public services provided to the community without the need to meet face-to-face. A simple way to find out the quality of e-Government in local governments is to look at the contents of the local government's official website. There are many website evaluation models, but they are still in stages/levels, with the weakness that if the first stage has not been fulfilled, it will be difficult for the Regional Government to "level up" in the next stage. The Fietkiewicz, Mainka, & Stock (2017) model sees that e-Government development is not limited to completion per level but more comprehensively presents each construction element as part of development progress. This model places the e-Government approach on a "pillar" approach, not a "tier" approach. The method used by the researcher is web observation with a qualitative approach. The results obtained from https://situbondokab.go.id., with a total of five pillars as indicators at 62% fulfilled from all the supporting elements of the pillars. Pillar of interoperability that obtains maximum value than other pillars. Meanwhile, the transaction pillar needs special attention from the Situbondo Regency Government for further web development. Keywords: e-Government; website; quality; pillar; Abstrak Sudah hampir 20 tahun Indonesia berkomitmen untuk meningkatkan digitalisasi pemerintahan melalui kebijakan e-Government. Kabupaten Situbondo sebagai lokus penelitian ini, pada tahun 2021 mendapatkan tiga penghargaan Top Digital Awards 2021 dari Majalah ITWorks karena keberhasilannya menjalankan sejumlah inovasi pelayanan publik berbasis digital. Inovasi pelayanan publik diantaranya juga perkembangan website. Website menjadi primary tool untuk melihat tingkatan penerapan e-Government di suatu pemerintahan daerah, pintu gerbang berbagai layanan publik yang diberikan kepada masyarakat tanpa perlu tatap muka. Cara sederhana untuk mengetahui kualitas e-Government pada Pemerintah Daerah adalah dengan melihat bagaimana isi website resmi Pemerintah Daerah tersebut. Ada banyak model evaluasi website namun masih berupa tahapan/tingkatan, dengan kelemahan jika tahapan pertama belum terpenuhi, maka sulit bagi Pemerintah Daerah untuk "naik tingkat" pada tahapan selanjutnya. Model Fietkiewicz, Mainka, & Stock (2017) melihat bahwa pengembangan e-Government tidak sebatas penyelesaian per tingkatan, tetapi lebih komprehensif menghadirkan setiap elemen konstruksinya sebagai bagian dari kemajuan pengembangan. Model ini menempatkan pendekatan e-Government pada pendekatan "pilar", bukan pendekatan "tingkatan". Metode yang digunakan oleh peneliti adalah observasi web dengan pendekatan kualitatif. Hasil yang diperoleh dari website Pemerintah Kabupaten Situbondo https://situbondokab.go.id., dengan total lima pilar sebagai indikator berada di angka 62% terpenuhi dari keseluruhan unsur unsur pendukung pilar. Pilar interoperability yang memperoleh nilai maksimal daripada pilar lainnya. Sementara pilar transaction perlu mendapatkan perhatian khusus dari Pemerintah Kabupaten Situbondo untuk pengembangan web selanjutnya. Keywords: e-Government; website; kualitas; pilar